Minimally Invasive Direct Coronary Artery Bypass: An Evolving Paradigm Over the Past 25 Years. Issue 6 (November 2022) - Varrone, Michael; Sarmiento, Iam Claire; Pirelli, Luigi; Brinster, Derek R.; Singh, Varinder P.; Kim, Michael C.; Scheinerman, S. Jacob; Patel, Nirav C.; Hemli, Jonathan M.
Objective: We have routinely utilized minimally invasive direct coronary artery bypass (MIDCAB) for revascularization of the left anterior descending (LAD) coronary artery. We examined how this procedure has evolved. Methods: A retrospective review was undertaken of 2, 283 consecutive patients who underwent MIDCAB between 1997 and 2021. Patients were divided into 3 groups: group A from 1997 to 2002 ( n = 751, 32.9%), group B from 2003 to 2009 ( n = 452, 19.8%), and group C from 2009 to 2021 ( n = 1, 080, 47.3%). Risk profiles and short-term outcomes were analyzed for the entire cohort and for 293 propensity-matched patients drawn from each group. Results: The left internal mammary artery was harvested open in group A but with robotic assistance in group C. Thirty-day mortality was higher in group A versus group C (12 deaths, 1.6% vs 5 deaths, 0.5%, P = 0.044); this difference was negated after propensity matching. Group A had more comorbidities than group C, including peripheral vascular disease (17.7% vs 10.0%, P < 0.001), congestive heart failure (39.6% vs 18.0%, P < 0.001), and a history of stroke (17.9% vs 10.0%, P < 0.001), although diabetes mellitus was more common in group C (51.4% vs 31.0%, P < 0.001). Stroke was greater in group A (1.2% vs 0.0% vs 0.2%, respectively, P = 0.004), as was the need for prolonged ventilation (3.6% vs 0.2% vs 0.9%, respectively, P < 0.001), before and after propensity matching. Conclusions: MIDCAB patients had less comorbidities than in the past. Robot-assisted MIDCAB was associated with lower stroke risk.